Rethinking curriculum in the linguistics component of a major on bilingual education (GIST – Education and Learning Research Journal, 2017)
The aim of this article is to report the partial findings resulting from a phenomenological study that intends to document the theoretical and empirical sources to inform a curricular proposal for the linguistic component of a major on bilingual education. From the theoretical point of view, this paper will present several perspectives about curriculum in tertiary education and the role of linguistics in a major on bilingual education. As for the empirical data, the paper will document how some professors in the second language teaching and linguistics fields, when analyzing the linguistic component of the curriculum in the major, advocate for a conscious use of metalanguage, the choice of content that empower student teachers to build their praxis and compete in their field,  the use of the first and second language for instruction, and a switch towards the problemic nature of the object of study rather than the subdiscipline fragmentation of knowledge. This paper also triangulates some of the participants’ perspectives with existing theory in an attempt to reach more informed grounds for a curricular proposal.
Keywords: linguistics; curriculum; bilingual education; tertiary education